Leadership styles and their role in strategic decision-making - Iryani, Novi; Suparno, Suparno; Saparuddin, Saparuddin (Jurnal Mantik, 2025)
This research discusses the role of leaders in strategic decision-making in companies, focusing on strategy implementation and the influence of leadership styles on strategic decisions. The purpose of this study is to analyze how transformational, transactional, democratic, and autocratic leadership styles influence the decision-making process and its outcomes. The method used in this research is a qualitative approach with a literature review, which collects, analyzes, and synthesizes information from various scientific sources related to strategic management and leadership. The results show that transformational leadership style has a significant positive influence on decision-making effectiveness, as it can increase employee motivation and engagement. Meanwhile, the transactional leadership style is more effective in short-term decision-making, and the democratic style is less effective in strategic decision-making because leaders are not actively involved in the process. At the same time, the autocratic style is highly dominated by the leader in determining decisions in the company. This study also concluded that leaders who can adapt their leadership style to the dynamics of the organizational situation can improve the performance and long-term competitiveness of the organization. These findings provide insights for companies in choosing the right leadership style to support the implementation of corporate social responsibility and more effective decision-making